Rancang Bangun CNC Plasma Cutting - Irfan, Saiful; Rusiyanto, Rusiyanto (Jurnal Rekayasa Mesin, 2021)
This study aims to determine the frame safety factor and the precision level of CNC plasma cutting results. The research method used is a research and development model, namely the French model. This model has 8 steps that are used to produce a CNC plasma cut design. The data analysis technique used is descriptive statistical analysis techniques derived from the results of tests conducted. Safety factor testing was conducted using the 2015 Autodesk Inventor software with a frame of 110.54 N. The precision cutting results were carried out three times using the same instrument, 20 currents with a speed of 400 mm/min, against ST 37 material with a thickness of 1.3 mm. The results showed that the frame was categorized as safe because the minimum safety factor value was 4.23 ul and the cut test results showed an average measurement with a maximum deviation of 0.3 mm, so it could be concluded that plasma CNC cutting had tolerance. rate of Â± 0.3 mm.